Dynamic diversity - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
Farmers safeguarding agricultural diversity through their crop husbandry compiled by Patrick Mulvany 1996 21 pp